Micro-takāful scheme for the protection of houses belonging to low-income groups in Malaysia - Puteri Nur Farah Naadia Mohd Fauzi; Mohamad Akram Laldin (ISRA International Journal of Islamic Finance, 2022)
Purpose - This study aims to assess the availability of micro-takāful (micro-Islamic insurance) schemes for the protection of houses belonging to low-income groups in Malaysia. Design/methodology/approach - The study is conducted via desk research and interview discussions with representatives from takāful operators and key stakeholders. Findings - Findings of the study confirm the importance of micro-takāful as a scheme for the protection of low-income groups. Micro-takāful schemes in Malaysia are, however, skewed towards the protection of health, life and family. The study finds little industry interest in the provision of micro-takāful schemes for the protection of houses for low-income groups. This represents another important area that takāful operators should take into consideration in their planning. Research limitations/implications - The paper will help the Majlis Agama Islam Negeri-Negeri (MAINs), the regulator, takāful operators and government agencies such as Jabatan Wakaf, Zakat dan Haji (JAWHAR) to generate awareness and promote the offering of micro-takāful schemes for the protection of houses belonging to low-income groups in Malaysia. Practical implications - In light of the limited availability of micro-takāful schemes for the protection of houses for low-income groups, this study argues that takāful operators should offer and promote them. Social implications - The study is significant for fulfilling the need of low-income groups in Malaysia to protect their houses in the event of catastrophes so that they will not suffer significant losses. Rather, micro-takāful will assist them in improving their standard of living. Originality/value - This study promotes the idea that it is essential to facilitate the low-income groups with appropriate coverage made available to them; micro-takāful schemes in protecting their houses and home contents, should any defined calamities occur. The outcomes are necessary for further development of micro-takāful models, specifically for the protection of properties. The developed model shall be proposed for application in the Malaysian takāful and housing industry to facilitate low-income groups to obtain protection for their household and home contents.
Keywords: 330; Insurance; Low-income groups; Micro-takāful; Properties; Protection